2003
DOI: 10.2337/diacare.26.3.650
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity and the Risk of Impaired Glucose Tolerance

Abstract: OBJECTIVE -Greater visceral adiposity, higher insulin resistance, and impaired insulin secretion increase the risk of type 2 diabetes. Whether visceral adiposity increases risk of impaired glucose tolerance (IGT) independent of other adipose depots, insulin resistance, and insulin secretion is not known. RESULTS -During the 10-to 11-year follow-up period, we confirmed 57 cases of IGT. Significant predictors of IGT included intra-abdominal fat area (IAFA) (odds ratio [OR] for a 1 SD increase 3.82, 95% CI 1.63-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(151 citation statements)
references
References 28 publications
4
145
0
2
Order By: Relevance
“…Studies carried out in different ethnicities showed that VAT, but not SAT, was strongly associated with the development of diabetes 16,17 and coronary heart disease. 18 Increased VAT was associated with impaired glucose tolerance 19 or insulin resistance. 20 The threshold values of VAT for the metabolic disorders differed among different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in different ethnicities showed that VAT, but not SAT, was strongly associated with the development of diabetes 16,17 and coronary heart disease. 18 Increased VAT was associated with impaired glucose tolerance 19 or insulin resistance. 20 The threshold values of VAT for the metabolic disorders differed among different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal adiposity per se is a specific and independent risk factor as regards insulin resistance, cardiovascular disease (3)(4)(5), glucose intolerance and type 2 diabetes mellitus (6,7). Moreover, adipose tissue is a source of free fatty acids (FFAs) and adipokines, such as adiponectin and resistin (5).…”
Section: Introductionmentioning
confidence: 99%
“…Adjustment for BMI, waist circumference, or HOMA-IR (a surrogate for insulin resistance) markedly attenuated these associations. Since adipose tissue is a major source of pro-inflammatory cytokines and greater visceral adiposity in Japanese descendants increases the risk of IGT at low BMI values [25], it is to be expected that abdominal adiposity weakens the association between CRP, IGT, and type 2 diabetes. This could explain why this attenuation effect was stronger on the association between CRP and type 2 diabetes, since newly diagnosed diabetic patients had higher proportion of abdominal obesity in this study.…”
Section: Discussionmentioning
confidence: 99%